(3OjhGf GdHRGRs - (3GdedG MSf Hf MSjf Hf Ydj GdHRGR,J (B1305 (3g` s
(3ChdgG (B:s
(3ddCOjH GdYGQa HGddg MSf CafOj GdHRGR gd GdCfS EdG HGfaQGOj hhMOJj Ce GdYR EdG aj NVhYj hPdJj s
(3BNQgG (B:s
(3adce UjOaj eZGfjg UjO HdMGX oJYqLd GdCNHGdG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B203s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B41 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs